Pembelajaran Mawaris dan Kemampuan Siswa dalam Pembagian Harta Warisan pada Madrasah Aliyah Negeri Kota Banda Aceh - Razak, Abdul; M. Nur, Azhar; Mardhiah, Ainal; Syahminan, Syahminan (Tadabbur: Jurnal Peradaban Islam, 2023)
The aim of this research is to determine the learning of inheritance, the ability to understand theory and the ability to practice the distribution of inheritance assets among Madrasah Aliyah students in Banda Aceh City. This research was conducted with a field study using qualitative descriptive methods. Data collection techniques are carried out through interviews, observation and documentation. The results of the research show that the learning of marais at Madrasah Aliyah Banda Aceh City is carried out by including the material of masaris in the RPP, and is also carried out with preliminary activities, core and closing activities, as well as providing evaluations to students. The students' ability to understand the theory of marasah Aliyah Madrasah Aliyah Banda Aceh in learning the jurisprudence of waris based on the description test given to students, it was found that 76 students got good grades, so it was concluded that 79.58% of the students from the 96 sample students had mostly mastered the material. Only a small number of students still need more in-depth enrichment regarding the reasons why someone is prevented from inheriting inheritance. It is known that the practical ability of dividing inheritance among Madrasah Aliyah students in Banda Aceh City has mastered the practice of dividing inheritance, this is proven by 73.9% of students answering the test questions correctly, and only a small portion of the sample answered incorrectly as many as 25 students or as many as 26.1 %